HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN STATUS GIZI BAYI USIA 6-12 BULAN DI POLINDES PATRANREJO BERBEK NGANJUK - MARIA, IIS (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2016)
Breastmilk provides all the energy and nutrients that needed by infants during the first 6 months after birth. But the scope of exclusive breastfeeding in Nganjuk still quite low and known that nutritional status problems is still very high. The purpose of this study was to determine the relationship of exclusive breastfeeding and nutritional status of infants aged 6-12 months in the Polindes Patranrejo Berbek Nganjuk. The design study is correlational with cross sectional approach. Samples are all mothers of infants aged 6-12 months in Polindes Patranrejo Berbek Nganjuk in 2014 were 34 mothers. The independent variable is exclusive breastfeeding, while the dependent variable is the nutritional status of infants aged 6-12 months. Data were collected through interviews and observation and then analyzed by Spearman Rank test at ? (0.05). The results showed that 19 mothers (55.9%) exclusively breastfed their babies, 24 infants (70.6%) infant nutrition status in the category of normal BB. Spearman Rank test results concluded that there is a relationship of exclusive breastfeeding and nutritional status of infants aged 6-12 months in the Polindes Patranrejo Berbek Nganjuk. Advised health workers to provide counseling and increase KP-ASI program, increasing malnutrition eradication program motion, giving KIE about breastfeeding, breastfeeding technique is correct, lactation management working mothers.Keywords :breastfeeding, exclusive, nutrient